The Impact of Art Therapy on School Students on One of After School Program - Alhumaidi, Dalal (My University, 2015)
Children can gain lot knowledge about themselves through expressive art therapy. They are likely to get in touch with their inner world and express their emotion and feelings. In our days there are some children who suffer from lack of communication with others, lack of attention from parents, less socialization, unhealthy psychological status and misconduct behavior. Art therapy been used among school age students at Boys and Girls Club Superior in Wisconsin to improve children emotionally, psychologically, socially, communicatively, behaviorally and developmentally. The results show that children were able to adopt new skills and knowledge about communicates and socialized communication and socialization with others, and more open to express their feelings and emotions.
Keywords: After School Programs; Socialization; Communication; Boys and Girls Club; Children; Art Therapy; Visual Arts